Urban Transport Sustainability: Asian Trends, Problems and Policy Practices - Hayashi, Yoshitsugu; Doi, Kenji; Yagishita, Masaharu; Kuwata, Masako (European Journal of Transport and Infrastructure Research, 2004)
The paper describes the possible direction of Asian EST, starting with an overview of recent trends and problems in transport systems within Asia, policy practices are also introduced. It was found that although the current situation and trend of transport in the Asian region presents a diverse picture stemming from geographical differences and levels of economic development, most Asian countries share similar concerns about transport-related problems, namely severe congestion, air and noise pollution,. Common patterns can be identified behind these problems, which include: a)large increases in traffic demand, resulting from rapid economic growth, urbanization, and motorisation, b)poor control of vehicle emissions and the absence of effective inspection and maintenance systems, c)lack of adequate and appropriate infrastructures, and d)poor coordination of transport and land-use policies. In the current situation, insufficient understanding of environmental deterioration mechanisms delay the implementation of necessary policy measures in many Asian countries. Each country should find the best way to achieve EST as fast as possible by learning from others’ experiences. Existing good examples within the region, such as intermediate public transport systems and electric road pricing, can provide a strong foundation for this purpose.